The enormous watermelon - Hawes, Alison (Cambridge : Cambridge University Press, 2016)
Ravi and Mum find an enormous watermelon. What should they do with it? In Red Band the sense of story starts to be developed. Illustrations continue to support understanding but readers also need to use decoding skills. Slightly longer texts with less repetition extend high-frequency word knowledge. Contains full teaching support including learning outcomes, curriculum links and follow-up activities.
Keywords: Children's - readers; Children's - stories